Response to “Comment on ‘Pinch current limitation effect in plasma focus’” - Lee, S.; Saw, S. H. (AIP Publishing, 2009)
The main point of the comment Appl. Phys. Lett. 94, 076101 2009 is that Eq. 2 and consequentially Eq. 3 of the commented paper Appl. Phys. Lett. 92, 021503 2008 require correction. The alternative equation suggested in the comment is derived using Kirchhoff’s voltage rule. The comment consider only the energy distribution in the inductive components and the resultant equation confirms a progressive lowering of the Ipinch / Ipeak ratio as the static inductance L0 is reduced, lowering from 0.87 to 0.31 as L0 is reduced from 100 to 5 nH according to the revised formula corresponding to Eq. 3, compared to 0.63–0.25 according to Eq. 3. This progressive lowering of the ratio Ipinch / Ipeak due to the inductive energy distribution is one of two factors responsible for the pinch current limitation. The other factor is the progressive reduction in the L-C interaction time compared to the current dip duration denoted by cap in Eq. 2. The comment does not deal with cap at all; hence, its conclusion based on inductive energy distribution only is not useful, since in the low L0 region when pinch current limitation begins to manifest, cap becomes more and more the dominant factor. In any case, the results of the paper do not depend on Eqs. 2 and 3, which are used in the paper only for illustrative purposes.